REPORT OF THE ANNUAL CONVENTION. - Cox, Carson (The Accounting Review, 1958)
Abstract The article reports on the annual meeting of the American Accounting Association (AAA) that was held on August 26-28 at the University of Wisconsin in Madison, Wisconsin. Major subjects covered at the sessions of the convention were accounting in industry, accounting theory and training for an accounting career. The round table topics discussed were techniques for handling increased enrollments, relationships and responsibilities of teaching staffs to executive department programs and short courses, reconsideration of the report of the Commission on Standards of Education and Experience, role of AAA to further the development of accounting theory, problems of students internships in public accounting, concepts and standards of income for taxation, the ideal course in elementary cost accounting and graduate programs in accounting. Special activities for the ladies included tours of the Cave of the Mounds, Little Norway, Oscar Mayer Packing Co. and a luncheon at the Nakoma Country Club. Activities for children consisted of a visit to Vilas Park Zoo, a fish hatchery and the Golden G. Ranch of the Bowman Dairy Co.